Potato production by using different potassium rates and vermi-wash spray applications - Mohamed A. ABDRABBO; Z. Y. MAHARIK; A. A. FARAG; M. ABUL-SOUD; M. A. FAHIM (Acta Agriculturae Slovenica, 2019)
The use of vermi-wash as organic source and potassium nutrients were investigated under this study. A field experiment was carried out during two successive summer seasons of 2017 and 2018 under open field conditions in Dokki experimental location, Agricultural Research Center, Giza Governorate, Egypt. The study aimed to evaluate the effect of applying different potassium rates 140, 280 and 420 kg K2O per hectare combined with spray vermi-wash for two, four, six times as well as spray water (control) on vegetative growth, yield of potato (Solanum tuberosum ‘Spunta’). The applications of potassium rates and vermi-wash sprays affected significantly the potato vegetative growth, total and marketable tuber yield as well as nutrient contents (N, P and K %) of potato leaves. Increasing potassium rate from 140 to 280 kg K2O per hectare enhanced total yield. Increasing potassium application to 420 kg K2O per hectare led to decrease the vegetative growth and productivity compared to 280 kg K2O per hectare.  Regarding the vermi-wash spray applications, data revealed that two times spray of vermi-wash enhanced vegetative growth and productivity, while increasing spraying of vermi-wash to more than two times led to decrease of potato vegetative growth and productivity.